2022
DOI: 10.3390/ijerph19063732
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing Professors’ Adaptation to Digital Learning Environments during the COVID-19 Pandemic

Abstract: This paper conducts quantitative research on the influence of the COVID-19 pandemic on the adaptation to digital learning environments (DLE) of a group of 908 university professors. We compared the perceptions of participants who were digital natives (born before 1980) with those of digital immigrants (born after 1980). For this purpose, a validated survey was used and the obtained responses statistically analyzed. The results show a negative correlation between pandemic stress and the digital competence of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 96 publications
3
34
0
2
Order By: Relevance
“…Numerous studies have found that the migration to digital environments of teaching processes caused by the pandemic has increased the workload of teachers and has generated difficulties in adapting to online environments, which has generated levels of anxiety associated with teaching [ 29 , 55 , 56 , 57 ]. There are also studies that corroborate that pandemic stress has had an impact on the adaptation to digital environments of university students in different areas of knowledge [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have found that the migration to digital environments of teaching processes caused by the pandemic has increased the workload of teachers and has generated difficulties in adapting to online environments, which has generated levels of anxiety associated with teaching [ 29 , 55 , 56 , 57 ]. There are also studies that corroborate that pandemic stress has had an impact on the adaptation to digital environments of university students in different areas of knowledge [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve the objectives of this study, a survey of 38 questions or items was used. The survey was designed for this purpose and based on the instrument developed in [ 29 ] for the measurement of digital pandemic stress on professors. This survey was employed to measure the values of the different dependent variables defined as indicated in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching staff must hold cognitive and motivational competencies [ 47 ], such as pedagogical skills, content knowledge, and general pedagogical knowledge [ 48 ]. To cope with the stress in classical and online education, staff need to develop methodological competencies, soft skills, and digital competencies [ 49 ]. This means that they must learn fast and be able to use data processing and protection tools, collaborative techniques in digital environments, and know how to create digital content and/or artistic multimedia output design and how to implement online assessments, etc.…”
Section: Hypothesis and Conceptual Model Developmentmentioning
confidence: 99%